Przebaczenie grzechów w nauczaniu Jana Chryzostoma. Zarys problematyki - Szczur, Piotr (Vox Patrum, 2015)
This article attempts to show the teaching of John Chrysostom (c. 350-407) on the mercy of God and His love for mankind, which manifests itself in the forgiveness of sins. God loves all people, but sometimes allows them to suffer in order to bring them closer to Himself and show them His love (Chrysostom uses here the image of the father and the doctor). The loving closeness of God is an invitation for sinners to return to their loving Father. The Church is an area of activity of the merciful God. It is in the Church that the sinner can obtain forgiveness by practicing repentance. However, the return to the merciful Father cannot be limited to an act of will, but the decision of will must be followed by action – concrete attitude expressing a real desire to implement the decision.